(untitled) (Research, Society and Development, 2023)
The Dravet syndrome (DS) is a genetically rare disease, also known as severe myoclonic epilepsy of childhood, associated with motor and behavioral comorbidities such as hyperactivity, sleep disturbance, deficits in social interaction and sudden death. There is a need for therapeutic approaches that control Dravet syndrome, as available conventional antiepileptic drugs have low efficacy. Therefore, the present work aimed to describe the therapeutic potential of cannabidiol to treat Dravet syndrome. Cannabidiol is a substance derived from the plant cannabis sativa that acts on the central nervous system and has been gaining ground in medicine to treat different diseases such as disorders in muscle control, tics, neuropathic pain, tuberous sclerosis, epileptic encephalopathy, among other pathologies. According to the studies cited in this work, cannabidiol to treat Dravet syndrome has demonstrated effectiveness from doses of 20mg/kg/day and CBD has shown efficacy when used in the long term. In addition to the decrease in seizures, comorbidities associated with the pathology were also reduced after cannabidiol administration. This work is an integrative review, the databases used were PubMed and ScienceDirect. 5 PubMed articles and 1 ScienceDirect article were included in the final sample. The descriptors were used: Epilepsies Myoclonic and Cannabidiol in Portuguese, English and Spanish that were combined with the Boolean operator “AND”. It is concluded that cannabidiol administered with appropriate dosages is effective to treat severe childhood epilepsy, including seizures and comorbidities associated with pathology in different age groups.